Pengaruh Kecepatan Pengadukan Terhadap Penyerapan Zat Warna Methyelene Blue Oleh Selulosa Dari Limbah Kulit Durian (Durio Zibethinus Murr) - Heditama, Muhammad Raffi; Nasra, Edi; Amelia, Fitri; Kurniawati, Desy (Periodic, 2024)
Methylene Blue is a dangerous dye produced in the textile industry. Biosorption can be used as one method to overcome textile dye waste. Biosorption is an easy-to-use method, because it is simpler, more economical, and environmentally friendly. Biosorbents that can be used, namely cellulose in durian peel (Durio zibethinus Murr.) can be used as an alternative to be used as a biosorbent in the absorption of methylene blue dyes. The purpose of this study was to determine the effect of stirring speed on the absorption of Methylene blue dye using cellulose adsorbents. In the study, methylene blue biosorption was carried out using durian peel cellulose biosorbent (Durio zibethinus Murr.) with a batch method at variations in stirring speeds of 50, 100, 150, 200, and 250 rpm. The results of this study obtained a cellulose extract from 90 grams of durian peel the extract resulted in 28.585 grams with a percentage of 31.69%. Results obtained at a speed of 200 rpm obtained an optimum absorption capacity of 25,0948 mg/g.